ANALISIS PENGARUH DIVERSITAS DEWAN KOMISARIS TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2018) - Gohanna Sondang M. Damanik; Totok Dewayanto (Diponegoro Journal of Accounting, 2021)
This study aims to obtain empirical evidence and analyze the effect of  the board of commissioners’ diversity, such as gender diversity, independent board of commissioners, the board of commissioners’ nationality, board of commissioners’ age, board of commissioners’ education, and managerial ownership on corporate social responsibility (CSR) disclosure. This study also uses profitability as a control variable.The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. The total sample used in this study was 85 companies based on predetermined criteria (purposive sampling). Data were analyzed using panel data analysis. The findings of this study indicate that gender diversity and board of commissioners’ education have a positive and significant effect on corporate social responsibility (CSR) disclosure, meanwhile independent board of commissioner, the board of commissioners’ nationality, board of commissioners’ age, and managerial ownership have no effect on corporate social responsibility (CSR) disclosure. Profitability as a control variable has no effect on corporate social responsibility (CSR) disclosure.